2018
DOI: 10.1101/491597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated transcriptomics and metabolomics analysis of theCucurbita peponectary implicates key modules of primary metabolism involved in nectar synthesis and secretion

Abstract: Nectar is the main reward that flowers offer to pollinators to entice repeated visitation. Cucurbita pepo (squash) is an excellent model for studying nectar biology, as it has large nectaries that produce large volumes of nectar relative to most other species. Squash is also monoecious, having both female and male flowers on the same plant, which allows comparative analyses of nectary function in one individual. Here we report the nectary transcriptomes from both female and male nectaries at four stages of flo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Previous studies have shown that degradation of nectary starch occurs simultaneously with the production of nectar sugar in many species (Nepi et al, 1996;Peng et al, 2004;Ren et al, 2007;Lin et al, 2014;Solhaug et al, 2019). In order to further examine starch metabolism in C. pepo nectaries, we first asked whether the starch was degraded during the dark period immediately preceding nectar secretion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that degradation of nectary starch occurs simultaneously with the production of nectar sugar in many species (Nepi et al, 1996;Peng et al, 2004;Ren et al, 2007;Lin et al, 2014;Solhaug et al, 2019). In order to further examine starch metabolism in C. pepo nectaries, we first asked whether the starch was degraded during the dark period immediately preceding nectar secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Some species, such as Arabidopsis (Arabidopsis thaliana), produce nectar rich in hexoses (Davis et al, 1998). Other species, such as tobacco (Nicotiana tabacum; Ren et al, 2007) and squash (Nepi et al, 2001;Solhaug et al, 2019), produce nectar rich in Suc. Previous research has shown that squash (Cucurbita pepo) cultivars with a higher Suc/hexose ratio in their nectar have increased pollinator visits compared with cultivars with lower Suc relative to hexoses (Roldán-Serrano and Guerra-Sanz, 2005), suggesting that composition of nectar sugar can influence pollinator visitation, which has also been shown to have a direct impact on fruit yield (Motzke et al, 2015;Pereira et al, 2015;Zou et al, 2017).…”
mentioning
confidence: 99%
See 3 more Smart Citations